Dietary factors leading to thiamine deficiency in salmon - Keinänen, Marja; Vuorinen, Pekka J. (My University, 2012)
Salmonid species that suffer from thiamine deficiency contain high fat concentrations. Thiamine deficiency occurs when they have an unbalanced diet principally consisting of one prey fish species, and when very few prey species overall are available in their feeding ground. The fat content of the main prey fish species of these salmonids is typically high, and can vary widely according to the season and also between areas, and evidently in relation to the feeding conditions. Thiamine deficiency has been linked to variations in the stock size of the main prey species, and some year classes of prey species tend to be most abundant. In most cases, a low egg thiamine concentration or high yolk-sac fry mortality has been associated with a high body weight or condition factor of salmon females. This indicates that salmon whose offspring display thiamine deficiency symptoms and mortality have access to copious amounts of food or/and food rich in energy. In the Baltic Sea, the thiamine concentration of both of the main prey species of salmon, sprat (Sprattus sprattus) and herring (Clupea harengus membras), is lowest in the youngest age groups (and also in the oldest herring, although these are not frequently included as salmon prey). Because the average fat content and energy density are greater in sprat than in herring, and greatest in the youngest sprat, the supply of thiamine per unit energy is lowest in a diet containing many young sprat. In the Baltic Sea, the thiamine content per unit fat and energy in the diet of salmon has been lowest during the years and in the areas where the recruitment and biomass of sprat have been high. Although the thiamine concentration of prey fish has been high enough for growth, the M74 syndrome is associated with a limited supply of thiamine in proportion to the supply of fat; i.e., a low ratio of thiamine to energy. Thus, thiamine deficiency in salmon eggs results from an unbalanced diet abundant in fatty prey fish, from which the supply of thiamine is insufficient in proportion to the supply of energy and unsaturated fatty acids for salmon, which undergo a prespawning fasting period.
Abstrakti
Keywords: M74-oireyhtymä; Itämeri; lohi; lisääntymishäiriöt; tiamiini